Korean-English Bilingualism in Early Childhood A Longitudinal Investigation of Development - Park-Johnson, Sunny K. (Bilingual Education & Bilingualism, 2024)
This overview of the linguistic development of Korean-English bilingual children in the US focuses on morphology and syntax acquisition in early childhood, a time when language dominance is shifting rapidly. It expands our understanding of heritage language acquisition and furthers bilingualism research on typologically distinct language pairings